Transition towards a social market economy? Limits and opportunities - Joachim Ahrens (OrdnungsPolitisches Portal (OPO), 2008)
The quest for an appropriate development and transition strategy in less developed countries (LDCs) and post-socialist countries (PSCs) has been studied for a long time, and it has been subject to numerous controversies among academics and development practitioners alike. Disputes have existed with respect to sequencing, timing, and pacing reforms, regarding the components of stabilization-cumadjustment programs, and also relating to the question which actors can become effective drivers of transition and development. Today, a widespread consensus exists that institutions and governance matter for making market-oriented policy reform succeed and that governments, despite the general need for less state interventionism, remain central actors for institution building and rule enforcement. The following considerations focus on the question whether or not the concept of the Social Market Economy, as it was originally developed and designed by German academics and policymakers more than fifty years ago, will be appropriate to guide policy and institutional reform in LDCs and PSCs and to make market-oriented reforms a viable policy choice in such countries regardless of their political regime.
Keywords: 330; Less developed countries; post-socialist countries; transition; social market economy